Nanotechnological Strategies to Improve Antifungal Therapy - C. Amaral, A.; S.S. Felipe, M. (Recent Patents on Nanomedicine, 2013)
Because of the increasing number of cases of mycosis that are resistant to treatment and the incidence of fungal infections, there is an urgent need to develop new and efficient drugs for antifungal therapies. Because the development of new drugs is expensive and time consuming, one strategy is the use of nanotechnology for drug delivery systems to prolong the use of the currently available antifungal agents. Several efforts are being expended to achieve these goals. In this review, some examples of patents filed that claim the development of nanostructured drugs, primarily through the use of liposomes, polymeric nanoparticles and nanomaterials that possess antimicrobial activity, are presented. In addition to the presented examples, there are many possibilities to be explored in this field for developing new treatment choices to prevent and even to cure important global diseases, such as mycosis.
Keywords: mycosis